Embodiment Effects and Language Comprehension in Alzheimer's Disease. (21st October 2014) - De Scalzi, Marika; Rusted, Jennifer; Oakhill, Jane
Abstract It has been shown that when participants are asked to make sensibility judgments on sentences that describe a transfer of an object toward or away from their body, they are faster to respond when the response requires a movement in the same direction as the transfer described in the sentence. This phenomenon is known as the action compatibility effect (ACE). This study investigates whether the ACE exists for volunteers with Alzheimer's disease (AD), whether the ACE can facilitate language comprehension, and also whether the ACE can still be produced if the order of the two events is inverted, that is, whether overt movement can prime comprehension of transfer sentences. In Study 1, participants with AD, younger, and older adults were tested on an adaptation of the ACE Paradigm. In Study 2, the same paradigm was modified to include an arm movement that participants had to perform prior to sentence exposure on screen. In Study 1, young, older adults, and individuals with AD were faster to respond when the direction of the response movement matched the directionality implied by the sentence (ACE). In Study 2, no traditional ACE was found; participants were faster when the direction of the movement immediately preceding the sentence matched the directionality of the sentence. It was found that compatibility effects generated a relative advantage, that transfer schemata are easier to process, and that an ACE‐like effect can be the result of mutual priming between language and movement. Results suggested preservation in AD of the neural systems for action engaged during language comprehension, and conditions under which comprehension in AD can be facilitated in real life may be identified.